Pulmonary thromboembolism presenting with multiple cavitary infarcts: A diagnostic challenge with overlap to granulomatous vasculitis - Akhan, Bilge Sezin (Acta Medica, 2026)
Pulmonary embolism (PE) is a life-threatening condition that can present with a wide range of symptoms, often complicating its diagnosis. Pulmonary infarction (PI), a rare consequence of PE, may mimic other conditions such as pneumonia, malignancy, or vasculitis. A 65-year-old woman presented with progressive dyspnoea, chest pain, and haemoptysis. She was initially diagnosed with pneumonia; however, imaging revealed cavitating pulmonary infarcts. Further investigations excluded tuberculosis, fungal and viral infections, as well as granulomatosis with polyangiitis presenting with multiple cavitary lesions. Contrast-enhanced CT pulmonary angiography confirmed the diagnosis of PE with multiple cavitary infarcts. The patient was treated with anticoagulation and broad-spectrum antibiotics, resulting in complete clinical and radiological resolution within eight months. This case highlights the importance of considering infected cavitary pulmonary infarction in the differential diagnosis of rapidly cavitating pulmonary lesions, particularly in the presence of clinical signs of infection, to avoid misdiagnosis and ensure appropriate management.